Remoção de CO2 em argilas bentoníticas e zeólitas ZSM-5 modificadas com aminas - Aquino, Rafael Batista de (2021)
The increase in greenhouse gas emissions has caused irreparable damage to the environment. Global agreements were and are being signed to try to limit the emission of these gases and, consequently, the increase in the global average temperature. Among the main causes of global warming are the large emissions of carbon dioxide (CO2), coming mainly from industries and fossil fuel combustion. In Brazil, the main emissions are from thermoelectric plants, livestock and the extraction of gases from the pre-salt layer, among other sectors of the industry. Currently, the main method for CO2 capture has been chemical absorption with liquid amines, but this method has caused severe inconveniences for industry and the environment. So researching alternative methods for CO2 removal is of fundamental interest to minimize the impacts of chemical absorption with liquid amines. Therefore, based on these observations, a method that stands out is the adsorption on porous materials or the use of these as a support for the impregnation of liquid amines that will be used in the removal of CO2. The X-ray diffractogram for the synthesized ZSM-5 evidences the characteristic peaks of this material and the ZSM-5 impregnations with 15, 30 and 45% amines maintained the characteristic peaks after impregnation. In the thermogravimetric analysis of ZSM-5 without impregnation it is possible to verify the stability of the zeolite structure. Observing the thermogravimetric curves for the impregnated ZSM-5, there were losses related to the amines inserted in the zeolitic structure. The X-ray diffractograms of the natural, chemically treated (TQ) and TQ+ impregnated clays, indicate the characteristic peaks for the clay mineral montmorillonite. The thermal stability of clays is demonstrated in thermogravimetric curves. The specific area for PMT-3 TQ and PMT-3 30% are 3.8 and 1.3 (m2/g), respectively. Among the natural clays, the one with the highest CO2 adsorption capacity was PMT-3 with 12 (mg CO2/g adsorbent), for the thermally treated ones, the one with the highest CO2 adsorption capacity was PMT-3 TQ with 16 (mg CO2/g of adsorbent), with an addition of 20%. The 30% PMT-3 impregnated clay obtained an increase of approximately 30%, with the value of 23 (mg CO2/g of adsorbent). ZSM5 zeolite has an adsorption capacity of 23 (mg CO2/g adsorbent) and after impregnation it increased to 40 (mg CO2/g adsorbent).